PERANCANGAN DESAIN MERCHANDISE UNTUK LOMBA LAYANG-LAYANG BERSAMA ENYO STUDIO - Pusaba, Wahyu (Program Studi Desain Komunikasi Visual, 2024)
Enyo studio is a creative company founded in 2019 which is managed by Putu Windu Subuat. Enyo Studio is located on Jl. Tukad Batanghari X, Panjer, South Denpasar, Bali. One of Enyo Studio's businesses is in the fashion sector with the name Zaloukh apparel, a business company in the fashion sector which was founded in 2020. In designing illustrations for merchandise, the theme is Balinese cultural traditions, namely Balinese Kites. Bali Kites can be one of the tourist attractions in Bali. This tradition is usually found in certain seasons ranging from June to September. Therefore, by using merchandise, information about the Balinese Kite Tradition can be conveyed well and become a promotional medium that can create curiosity and interest in Balinese traditions, especially for foreign tourists visiting Bali. So tourists can buy this merchandise as a reminder or memento of Bali.